2018
DOI: 10.3390/toxins10070294
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Mycotoxin Occurrence in Dairy Cattle Feeds from the Gauteng Province of South Africa: A Pilot Study Using UHPLC-QTOF-MS/MS

Abstract: The indispensable nature of toxigenic fungi and mycotoxins in agricultural systems is of worldwide concern, hence the need for surveillance studies to preserve public health. Thirteen dairy farms were surveyed and 40 dairy feeds of varying nature collected and analyzed for mycotoxins. Estimated levels of aflatoxins (AFs), fumonisin B1 (FB1), ochratoxin A (OTA), citrinin (CIT), zearalenone (ZEN), α-zearalenol (α-ZEL), β-zearalenol (β-ZEL), deoxynivalenol (DON), 3- and 15-acetyl-deoxynivalenol (ADONs), HT-2 toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 53 publications
3
33
1
1
Order By: Relevance
“…Zearalenone was also reported in maize samples from Cameroon with a mean concentration of 68 µg/kg and a maximum concentration of 309 µg/kg [70]. However, the relatively low level of ZON observed in this study somewhat supports the notion that ZON is perhaps a persistent yet minor contaminant of foods/feeds in South Africa [66,69,71] but its significance is in its oestrogenic potential to mammals.…”
Section: General Mycotoxin Occurrence Datasupporting
confidence: 55%
“…Zearalenone was also reported in maize samples from Cameroon with a mean concentration of 68 µg/kg and a maximum concentration of 309 µg/kg [70]. However, the relatively low level of ZON observed in this study somewhat supports the notion that ZON is perhaps a persistent yet minor contaminant of foods/feeds in South Africa [66,69,71] but its significance is in its oestrogenic potential to mammals.…”
Section: General Mycotoxin Occurrence Datasupporting
confidence: 55%
“…Taking into account the feed and food shortage in SSA, spoiled and moldy maize that has been considered unfit for human consumption is often fed to animals [22,23]. Both fodder and concentrates have been reported to be contaminated with mycotoxins, with the latter being the major source of contamination [11,[24][25][26]. This makes all dairy farming practiced in SSA at risk of contamination with mycotoxins.…”
Section: Incidence Of Mycotoxins In Dairy Feed In Sub-saharan Africamentioning
confidence: 99%
“…Aflatoxins (AF) produced by Aspergillus species, fumonisins (FUM), zearalenone (ZEN), T-2 toxin (T-2), and deoxynivalenol (DON) produced by Fusarium species, and ochratoxin A (OTA) produced by Aspergillus and Penicillium species are well-known mycotoxins of major agricultural importance and have been found concurrently occurring in feeds, with AF, which is a class 1 carcinogen to human beings, the most prevalent and also the most studied in SSA [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Dairy farming is affected as a result of feed contamination, the risks posed to animals' health, affecting productivity and animal performance, and the ability of these contaminants to reach the human diet through animal by-products, such as meat and milk, compromising public health. 1 Although the rumen is supposed to be a barrier against mycotoxin contamination, reports have demonstrated that the carry-over of mycotoxins into the milk is possible in some cases. 2,3 Limited studies have been developed for monitoring mycotoxins in milk besides AFM1, commonly considered to be a detoxication by-product of AFB 1 .…”
Section: Introductionmentioning
confidence: 99%